2019
DOI: 10.1016/j.ctro.2019.01.001
|View full text |Cite|
|
Sign up to set email alerts
|

An in-silico quality assurance study of contouring target volumes in thoracic tumors within a cooperative group setting

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…In the PET-plan trial's dummy run, GTV volume and overlap metrics showed significant IOV before and after an additional teaching session [30]. The Southwest Oncology Group (SWOG), observed a median DSC for nodal GTV of only 0.35 as the target definition was highly uneven among participants [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the PET-plan trial's dummy run, GTV volume and overlap metrics showed significant IOV before and after an additional teaching session [30]. The Southwest Oncology Group (SWOG), observed a median DSC for nodal GTV of only 0.35 as the target definition was highly uneven among participants [10].…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation for the persistence of IOV may be the lack of description of the anatomical differences between contours in many studies which mainly reported numerical expressions of IOV [6,9,10], instead of the information required for clinicians to adapt their methods. Furthermore, quantitative approaches used to analyze the quality of TVD [11] are generally applied to a reference 4 volume generated from multiple observers' inputs [12,13] irrespective of their similarity.…”
Section: Introductionmentioning
confidence: 99%